2021
DOI: 10.1111/ijcp.14854
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 polyunsaturated fatty acids supplementation improve clinical symptoms in patients with Covid‐19: A randomised clinical trial

Abstract: Aims:We hypothesised that omega-3 fatty acids would be an appropriate adjunct therapy for alleviating the inflammatory response and clinical manifestation in hospitalised patients with Covid-19 disease. Methods: This was a single-blind randomised controlled trial in Amir-Alam hospital in Tehran. Thirty adult men and women diagnosed with Covid-19 were allocated to either control group (receiving Hydroxychloroquine) or intervention group (receiving Hydroxychloroquine plus 2 grams of Docosahexaenoic acid [DHA] + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
0
31
0
1
Order By: Relevance
“…We included four studies [ 26 , 31 33 ] in this meta-analysis, totaling 274 COVID-19 patients. Patients were randomly assigned to receive Omega-3 or other derivatives as an intervention or control in all trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included four studies [ 26 , 31 33 ] in this meta-analysis, totaling 274 COVID-19 patients. Patients were randomly assigned to receive Omega-3 or other derivatives as an intervention or control in all trials.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the randomization process, two included studies [ 26 , 32 ] reported an adequate randomization method with allocation concealment, so we judged them as low risk. However, Sedighiyan et al[ 33 ] and Kosmopoulos et al [ 31 ] were judged as some concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, apart from having immune-modulating effects, n-3 FA supplementation may have beneficial effects on vascular endothelial function and microcirculation as evidenced by improvement in blood gas and renal function parameters. Sedhigiyan et al compared hydroxychloroquine treatment to hydroxychloroquine plus n-3 FAs and found that patients randomized to the latter regimen had statistically significantly improved myalgias and fatigue, and lower erythrocyte sedimentation rates and CRP levels (33).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing effects of omega-3 supplementation compared with control group were also observed in the levels of ESR and CRP after treatment. No differences in the liver enzymes serum concentrations were observed between groups after supplementation [ 102 ], IRCT20200511047399N1 Remdesivir Adults at the median age 58.9 ± 15 years, hospitalized with illness of any duration, with laboratory-confirmed SARS-CoV-2 infection in sample collected for less than 72 h prior to randomization A total of 1062 participants were enrolled in the study: 541 assigned to remdesivir and 521 to placebo Remdesivir was administered intravenously as a 200-mg loading dose on day 1, followed by a 100-mg maintenance dose administered daily on days 2 through 10 or until hospital discharge or death. A matching placebo was administered according to the same schedule and in the same volume as the active drug Patients were assessed daily during their hospitalization, from day 1 through day 29 Under this protocol, treatment with remdesivir was superior to placebo in shortening the time to recovery in adults who were hospitalized with COVID-19 and had evidence of lower respiratory tract infection (median 10 days as compared with 15 days) [ 114 ], NCT04280705 Molnupiravir Adults at the median age 40.8 years (18–82 years), non-hospitalized, but with confirmed active SARS-CoV-2 infection in a sample collected ≤ 96 h prior to study entry.…”
Section: Drugs Inhibiting Attachment Of the Virus To Host Cellsmentioning
confidence: 99%